Harmonics resonance elimination technique using active static compensation circuit - Rakan Khalil Antar; Mohammed Y. Suliman; Asef A. Saleh (Institute of Advanced Engineering and Science, 2021)
The existence of nonlinear loads produces high distortion and low power factor in the power system that leads to get poor power quality. Resonance problem is occurred due to the power system inductances and the compensation capacitors which increases the harmonic distortion. Therefore, it is necessary to prevent the action of resonance even if conventional or modern methods are built to improve the power system quality. In this paper, active static compensation circuit is proposed and designed to have the features of improving power factor, reducing THD, and eliminating the harmonics resonance effect at the same time with different linear and nonlinear load conditions. These features have been performed based on a modified pulse width modulation technique to drive and control the proposed circuit. The originality designed point of this technique is to have ability to operate the active static compensation circuit as harmonics injector, power factor corrector and resonance eliminator at the same time. Simulation model results illustrate that the proposed circuit is effective for both steady-state and transient operations conditions. The THD of the supply voltage and current at firing angle (α=300) is reduced by 99% and 98.8% respectively. While the power factor is improved to stay around unity.